Eviota fallax, a New Dwarfgoby from the Western Pacific (Teleostei: Gobiidae) - Greenfield, David W.; Allen, Gerald R. (Zootaxa, 2012)
Eviota fallax is described from West Papua, Indonesia and also is known from Bali, Banda, and Sangihe Island, Indonesia,New Britain, Solomon Islands, Yap, Ngulu Atoll, and the Ryukyu Islands, Japan. The species has an occipital spot (moreobvious in males and preserved specimens), a complete cephalic sensory-pore system (Group I), and a dorsal/anal formulaof 9/8, characters shared with E. karaspila, E. melasma, and E. smaragdus. It differs from these species in coloration, measurements and pelvic-fin structure.